Mathematisation of Thought: Right or Wrong Answer in Mathematics Classroom - Kushwaha, Madhu; Srivastava, Shubhrm (JOURNAL OF INDIAN EDUCATION, 2011)
According to the National Curriculum Framework, 2005, the aim of mathematics teaching is ‘mathematisation’ of thought, which means to be able to understand the world in the language of mathematics. Research suggests that stereotyped classroom teaching involves a mechanical or procedural approach to problem solving, with emphasis on getting a right answer. The children are hence socialized to approach a problem in procedural manner to get a legitimate correct answer without giving consideration to the realistic context of the problem. This paper studies the approaches of children studying in Class V of a reputed government CBSE school, to realistic mathematics word problems and how these approaches are related to their classroom achievement. The analysis of the responses reveals that the children approach the problems in a procedural manner and their school grades are not related to their realistic understanding of the problem.